Post-qualifying child care social work : developing reflective practice - Ruch, Gillian (SAGE, 2009)
This textbook provides an authoritative overview of the Post-Qualifying Child Care Award in social work. Written in response to policy and training guidelines, this title presents the underpinning knowledge for those candidates following the Post Qualifying curriculum.